Do cômico ao crítico nos processos de comunicação: o corpo do palhaço e a construção da criticidade - Correia, Eliana Rosa (2015)
This thesis aims to conduct an analysis of the processes of communication between comical and critical from the clown of the body, and see what this configuration space is the construction of contemporary social criticism. The issues that circumscribes refers to social transformations produced by the speed with which new forms of communication are made available by advances in technology. With these changes, we develop new cognitive habits and how the body and the environment relate co-evolutionary, if change also our society has changed, and the comic also lives moments of transformation. By understanding the comical clown body is a kind of critical high potential for speech, some comic characters sought this as a benchmark for acting in film and television. The get-together television presenter and film characters Carlitos Chaplin and Fellini's Cabiria, are examples because if constituted as cases in which the comic and humor, acted as a spark for criticism of society. Today in Brazil, the projection that sitcoms like CQC won Rede Bandeirantes, point out that the relationship between comedy and criticism in the Brazilian media, also won new approach. The theoretical framework of this thesis was based on the corpomídia the studies prepared by Christine Greiner and Helena Katz (2001), the discussion about the humorous company held by Lipovetsky (1989), in studies of laughter from Minois (2003), Bergson (1983) and Propp (1992) and works on the clown Bolognesi (2003) and Burnier (2001). The works of Muniz Sodre (1972), Aronchi (2004) and Thompson (1998) are shown also as fundamental to explain the Communication understanding that guides this research